The feeding process of Plasmodium falciparum in resealed erythrocytes containing endocytic markers and its role in artemisinin action - Zamri, Noor Hafizah Mohd (2018)
Haemoglobin metabolism during the intraerythrocytic stage of the malaria parasite, Plasmodium falciparum is a preferable target for artemisinin, which is widely used for treatment and control of malaria. It has previously been reported that the parasite ingests haemoglobin via mouth-like structures named cytostomes. Haemoglobin-containing vesicles that bud off from cytostomes are transported to the digestive vacuole (DV) where the haemoglobin is degraded. However, the details of endocytic process as well as how artemisinin affects this process are still debatable. Hence, in this study we re-examined the endocytic process of the parasite and observed the effect of artemisinin on this process by using an endocytic marker, tetramethylrhodamine-dextran (TMR-dextran) and a pH indicator, Lysosensor Blue (LB) and SNARF-1-dextran. Resealed erythrocytes containing TMR-dextran were prepared at an optimised ratio of 1:3 of erythrocytes to haemolysis buffer volume. The resealed erythrocytes permitted retention of 33.56 ± 7.84% of the original haemoglobin contents and showed comparable parasite‟s invasion efficiency to normal erythrocytes. An early endocytic event of the parasites was initiated at mid ring stage with appearance of typical small endocytic compartments and a large spherical structure termed as a “big gulp”. An acidic DV concentrated with TMRdextran and labelled with LB, appeared at the later stages of trophozoite and schizont. Artemisinin treatments on this process showed no modification on thehaemoglobin intake by the parasite and no alterations of the LB label and SNARF-1- dextran of the DV indicating no major pH changes of the vacuole. In conclusion, haemoglobin is ingested by the parasite at early intraerythrocytic stage and accumulated in the acidic DV where the vacuole showed no significant pH alterations upon the artemisinin treatments.